2021
DOI: 10.21203/rs.3.rs-951471/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Online, face-to-face, or blended learning? Faculty and medical students’ perception during the COVID-19 pandemic: A mixed-method study

Abstract: Background: The COVID-19 pandemic forced educational institutions to adopt online methods which were inevitable to keep the continuity of education across all academia after the suspension of traditional educational systems. The aim of this study was to explore the experience of faculty and students of online learning and their preference of the mode of learning after the pandemic.Methods: This is a mixed-method study that encompassed a quantitative component (researcher-made survey consisting of 22 items unde… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 23 publications
3
13
0
Order By: Relevance
“…However, within the context of learning public health concepts, we believe that hands-on training along with virtual learning would be more suitable. We propose, in line with the recommendations from other studies ( 21 , 27 ) to encourage educators to use hybrid strategies in order to improve the experiences of medical students in learning public health concepts.…”
Section: Discussionmentioning
confidence: 66%
See 2 more Smart Citations
“…However, within the context of learning public health concepts, we believe that hands-on training along with virtual learning would be more suitable. We propose, in line with the recommendations from other studies ( 21 , 27 ) to encourage educators to use hybrid strategies in order to improve the experiences of medical students in learning public health concepts.…”
Section: Discussionmentioning
confidence: 66%
“…The COVID-19 pandemic has enhanced the adoption of online distance learning after the suspension of traditional teaching due to closures and lockdowns. Several studies have indicated that theoretical parts of the medical curriculum can be taught via virtual strategies while the practical and clinical components would be better delivered via either face-to-face or preferably a mixed approach ( 20 , 21 ). Digital transformation of medical academic activities was mandated during the current COVID-19 pandemic and is likely to become the norm medium of the educational environment even in the post-COVID-19 era.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nonetheless, subsequently, the sense of responsibility toward teaching gradually facilitated accepting the situation and managing anxiety, stress, confusion, frustration, and helplessness toward this crisis, a sense of mental and physical insecurity to be able to fulfill teaching duties and responsibilities, as reported by Casacchia et al (2021) and Manar Nabolsi et al (2021).…”
Section: Personal Barriermentioning
confidence: 93%
“…As described in the summary of references in previous related research studies included in the introduction section of this paper (Section 1), the results and the basic conclusion of our research in general is in line with related published findings and conclusions (Dziuban et al, 2018;Means et al, 2010;Youngers, 2014). However, recently, especially in the era of pandemic covid-19, where on line learning or blended learning were implemented in a rough way even in audiencies where such a method is not considered as appropriate, there are some findings stating that face to face learning is preferable and more efficient for the learners (Atwa et al, 2022;Nasution et al, 2021).…”
Section: Overall Teacher Trainees' "Performance" (Regardless Of Teach...mentioning
confidence: 99%